Balloon effects in coca crops in the Andean region (1990-2009) - Raffo López, Leonardo; Castro, Javier Andrés; Díaz España, Alexander (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The aim of this article is to contrast empirically the presence of ballooneffects affecting coca crops in the geographic territory corresponding tothe main producer countries (Colombia, Perú and Bolivia) of the Andeanregion during the period 1990-2009. The empirical methodology has beenfocused in the specification and estimation of a simultaneous equation systemusing a SUR model. The model attempts to explain the behaviour ofthe number of hectares cultivated with coca plants as a function of differentvariables. We conclude that there is empirical evidence supporting the presenceof balloon effects in the Andean region during the period of inquiry.